Critical approaches to the production of music and sound - Bennett, Samantha (Music professor); Bennett, Samantha (Music professor); Bates, Eliot; Bates, Eliot (Bloomsbury Academic, 2018)
Who produces sound and music? And in what spaces, localities, and contexts? As the production of sound and music in the 21st century converges with multimedia, these questions are critically addressed in this new edited collection. This work features 16 brand-new articles by leading thinkers from the fields of music, audio engineering, anthropology, and media. Innovative and timely, this collection represents scholars from around the world, revisiting established themes such as record production and the construction of genre with new perspectives, as well as exploring issues in cultural and virtual production.